Persuasive strategies in the English translations of the al-Baqarah Quranic verses / Dalal A. S. Aldahshan - Dalal A. S. , Aldahshan (2020)
The persuasive act refers to the performance of an act with the use of a specific form of communication through language, one of the most essential factors used in influencing people's thoughts and attitudes, setting decisions and controlling values. The persuasive act can be used in many ways by influencing the thoughts and behavior of people or in advertisement which sell products or services by way of convincing people to buy certain products or services. In politics, it is also used to convince people to change their political beliefs or ideologies. On the religious side, the persuasive act is considered as one of the most effective methods used to convince the reader to adopt and observe certain religious beliefs and practices. This research aims to explore the various persuasive speech acts used in the longest chapter of the Holy Qur'an, that is, Surah (Chapter) Al-Baqarah. This study also attempts to describe and identify the rhetorical devices used in the acts of persuasion found in the chapter. By carrying out a pragmatic analysis based on Searle's classifications of speech acts (1979) and Johnstone's techniques of persuasion (2008), the data is analyzed linguistically by identifying the types of persuasive acts and the rhetorical devices used as strategies and techniques of persuasion. The results reveal that the speech act classes of assertives, directives and commissives are used in the Al-Baqarah chapter as persuasive strategies. Assertives are used to assert beliefs or to confirm and emphasize facts whereas directives are used to command, suggest, recommend or to encourage the reader as means to influence their attitudes or to perform actions of the persuasive discourse. The commissive type is also used as a means of persuasion through giving promises and encouraging the readers to perform certain actions. It is also found that there are combinations of two persuasive acts in one verse such as the assertive and directive types, the assertive and commissive types and the directive and commissive types. The findings also demonstrate the use of three persuasive techniques; quasilogical, presentational and analogical. Quasilogical argumentation, which is based on rationality, is utilized via conditional clauses, logical connectives and rhetorical question. To create involvement, the presentational persuasion is manipulated via repetition, rhetorical deixis and similes. The analogical technique of persuasion is also employed in the Holy Qur'an that is exemplified by the use of stories of the prophets.